2010
DOI: 10.1002/ange.201002690
|View full text |Cite
|
Sign up to set email alerts
|

Ein achtkerniger [CrIII4DyIII4]‐3d‐4f‐Einzelmolekülmagnet

Abstract: In memoriam Ian J. Hewitt Die Untersuchung der Synthese, Struktur und magnetischen Eigenschaften vielkerniger Koordinationscluster mit anisotropen paramagnetischen Zentren wurde seit der Entdeckung, dass sich solche Moleküle als Einzelmolekülmagnete (single-molecule magnets, SMMs) verhalten können, zu einem wichtigen Gebiet in der modernen Koordinationschemie.[1] Ein grundlegendes Charakteristikum des SMM-Verhaltens ist das Vorhandensein einer Energiebarriere bezüg-lich der Reorientierung der Spins im Grundzus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
3
14
1
Order By: Relevance
“…[14] for example, produced a number of Cu II -Ln III compounds with pyridonate ligands, whereas SMMs were recently reported for dinuclear CuTb, [13b,c,d] trinuclear CuDy 2 [15] and several tetranuclear Cu 2 Ln 2 (Ln = Dy and Tb) compounds. [16] Larger clusters such as CuDy 4 , [17] {Cu 3 Dy 3 } 2 , [18] Cu 6 Dy 3 [19] and Cu 24 Dy 8 [20] also display SMM behaviour. It is therefore apparent that heterometallic Cu-Ln clusters display SMM behaviour due to a combination of large-spin ground states, which are often observed, and a large anisotropy derived from the lanthanide ions.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…[14] for example, produced a number of Cu II -Ln III compounds with pyridonate ligands, whereas SMMs were recently reported for dinuclear CuTb, [13b,c,d] trinuclear CuDy 2 [15] and several tetranuclear Cu 2 Ln 2 (Ln = Dy and Tb) compounds. [16] Larger clusters such as CuDy 4 , [17] {Cu 3 Dy 3 } 2 , [18] Cu 6 Dy 3 [19] and Cu 24 Dy 8 [20] also display SMM behaviour. It is therefore apparent that heterometallic Cu-Ln clusters display SMM behaviour due to a combination of large-spin ground states, which are often observed, and a large anisotropy derived from the lanthanide ions.…”
Section: Introductionmentioning
confidence: 93%
“…During our previous work with teaH 3 , we showed that the cluster topology is highly dependent on the co-ligand used [22b] and here we have chosen pivalic acid as the coligand. We report the synthesis and magnetic properties of four isostructural Cu-Ln clusters of general formula [Cu 4 ]·3 CH 2 Cl 2 (mdea = methyldiethanolamine dianion, piv = pivalate), [24] yielded a set of isotropic coupling constants for Dy-Cu and Cu-Cu pathways that simulate well the susceptibility data. In a separate collaboration, Cu-Gd compound (1) has been shown to have a record value for the magnetocaloric effect (MCE) at low temperatures, compared to other spin-coupled molecular clusters.…”
Section: Introductionmentioning
confidence: 95%
“…On the other hand, much work has concentrated on mixing 4 f ions with anisotropic 3 d ions to prepare the former 3 d ‐based SMMs; however, some isotropic ions can also be favorable in 3 d –4 f coordination clusters with enhanced SMM properties . Since the [Cr III 4 Dy III 4 ] SMM was reported, 3 d –4 f SMMs containing Cr III ions have drawn great attention . More recently, a rare [Cr III 2 Dy III 2 ] SMM with a high U eff of 77 K and large coercive magnetic fields was synthesized, which can significantly reduce the quantum tunneling of magnetization (QTM) due to the exchange interaction between Cr III and Dy III ions .…”
Section: Introductionmentioning
confidence: 99%
“…DC magnetic susceptibility was measured for solid samples of 1-6 at 0.1, 0.5 and 1 T in the 1.8-300 K temperature range (Figure 3 [8,15] ). On decreasing the temperature (Figure 3, a) this value increases marginally to about 3.67 cm 3 K mol -1 at 18 K, then rises sharply to about 4.05 cm 3 K mol -1 at 2 K. Measurements at different static magnetic fields for compound 1 (H = 1, 0.5 and 0.1 T) show a field dependency of χT at low temperatures (Figure 3, a).…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…by Xu et al, [6] to obtain [CrLn 2 ] assemblies with 2-methyl-8-hydroxyquinoline acting as a ligand, while Kou et al [7] characterized a [Cr 2 Gd 2 ] cyano-bridged species. Rinck et al [8] provided an example of a [Cr 1 terized mainly by X-ray diffraction studies, EDX, elemental analyses, IR spectroscopy and studies of magnetic properties, the latter showing negligible coupling of the Cr 3+ ions in 1.…”
Section: Introductionmentioning
confidence: 99%